Konseling Daring bagi Mahasiswa Universitas Sebelas Maret, Surakarta, Indonesia - Siti Sutarmi Fadhilah; Agus Tri Susilo; Indriyana Rachmawati (Universitas Mathla'ul Anwar Banten, 2019)
ONLINE COUNSELING FOR STUDENTS OF UNIVERSITAS SEBELAS MARET, SURAKARTA, INDONESIA. The industrial revolution 4.0 resulted in disruptive changes that affected human life. Likewise, the students of Sebelas Maret University (UNS) in fulfilling their academic, personal, social, and career development assignments, also often demanded independence in this disruption era. As the third rank university in Indonesia, according to UniRank 4ICU rating agency, UNS needs to respond to this in order to be able to facilitate the task of developing students from the psychological side. Facilitation that can be done is by providing online counseling services for students. This study aims to describe the level of UNS student needs as initial data in compiling online counseling services. The subjects of this study were 544 students from ten faculties in the UNS that were randomly determined. The results of the analysis showed that the needs of student counseling services included six problem areas namely: personal-social (81%), academic (76%), career (82%), premarital (75%), traumatic (71%), and multicultural (81 %). The results of this study indicate that the level of need for online counseling services for UNS students is quite high. These results need to be followed up with the development of an android-based online counseling service platform in order to improve the quality of psychological services of UNS students.